2021
DOI: 10.1111/dth.14840
|View full text |Cite
|
Sign up to set email alerts
|

The impact of air pollution on skin and related disorders: A comprehensive review

Abstract: As the largest organ in the body, human skin is constantly exposed to harmful compounds existing in the surrounding environment as the first-line barrier. Studies have indicated that exposure to high concentrations of many environmental factors, such as ultraviolet (UV) radiation, outdoor air pollutants, including polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), particulate matter (PM), heavy metals, gaseous pollutants, such as carbon monoxide (CO), nitric oxides (NO x ), sulfur oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 95 publications
1
47
0
Order By: Relevance
“…The most common air pollutants comprise polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs, e.g., benzene), particulate matter (PM, most commonly PM2.5 and PM10), gaseous pollutants, (carbon-monoxide, nitric oxides, sulphur oxide, ozone, heavy metals) and indoor pollutants, as solid fuels consumption 8 . Although the molecular mechanisms relating air pollutions to skin diseases are not yet fully understood, several in vivo studies have highlighted the occurrence and prominence of the inflammatory state as a common factor of these conditions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The most common air pollutants comprise polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs, e.g., benzene), particulate matter (PM, most commonly PM2.5 and PM10), gaseous pollutants, (carbon-monoxide, nitric oxides, sulphur oxide, ozone, heavy metals) and indoor pollutants, as solid fuels consumption 8 . Although the molecular mechanisms relating air pollutions to skin diseases are not yet fully understood, several in vivo studies have highlighted the occurrence and prominence of the inflammatory state as a common factor of these conditions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…As an example, there are no clinical studies linking air pollution and psoriatic arthritis, despite the robust association between cigarette smoking and psoriasis that has been demonstrated, 40 and a few studies have shown a possible detrimental effect of air pollution on psoriasis extension. 41 Another example comes for systemic sclerosis. Air pollution exposure has been linked with higher burden of Raynaud phenomenon and pulmonary manifestations, 42 but no solid RMD Open RMD Open RMD Open evidence has been produced regarding the association between exposure to traffic-derived pollutants and the risk of developing systemic sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The skin is also at increased risk for negative effects from air pollution. Albeit a direct link between pollutant exposure and eczema incidence has not been fully elucidated, exposure has been associated with eczema exacerbation, cellulitis, and increased incidence of skin cancer (Abolhasani et al, 2021). Li, Fan, Xie, Ren, & Li (2018) identified a positive correlation between exposure to unhealthy air and acute health care visits for eczema exacerbation.…”
Section: Childhoodmentioning
confidence: 99%